2015
DOI: 10.1161/atvbaha.115.305969
|View full text |Cite
|
Sign up to set email alerts
|

Orai3 Surface Accumulation and Calcium Entry Evoked by Vascular Endothelial Growth Factor

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…Similar to other endothelial cells types [ 108 , 109 ], SOCE is constitutively activated to refill the InsP 3 -dependent ER Ca 2+ pool and maintains basal Ca 2+ levels in mouse brain microvascular endothelial cells [ 76 ]. AA may induce extracellular Ca 2+ entry in vascular endothelial cells by prompting Orai1 to interact with Orai3 independently on Stim1 [ 110 ]. Nevertheless, Orai3 is not expressed in bEND5 cells, and therefore, this mechanism is unlikely to work in NVC [ 76 ].…”
Section: The Role Of Endothelial Ca 2+ Signalinmentioning
confidence: 99%
“…Similar to other endothelial cells types [ 108 , 109 ], SOCE is constitutively activated to refill the InsP 3 -dependent ER Ca 2+ pool and maintains basal Ca 2+ levels in mouse brain microvascular endothelial cells [ 76 ]. AA may induce extracellular Ca 2+ entry in vascular endothelial cells by prompting Orai1 to interact with Orai3 independently on Stim1 [ 110 ]. Nevertheless, Orai3 is not expressed in bEND5 cells, and therefore, this mechanism is unlikely to work in NVC [ 76 ].…”
Section: The Role Of Endothelial Ca 2+ Signalinmentioning
confidence: 99%
“…These discrepancies could reflect the well known heterogeneity in terms of Ca 2+ signalling between hECFCs and mature endothelium [74]. However, AA has recently been shown to induce a robust Ca 2+ release in human umbilical vein ECs (HUVECs) when applied at >10 M [26].…”
Section: Arachidonic Acid Utilizes Intracellular Ca 2+ and No Signalsmentioning
confidence: 99%
“…The Ca 2+ response to AA in other cellular models is more complex and involves additional pathways, including: inositol-1,4,5-trisphosphate (InsP 3 ) receptors (InsP 3 Rs) and ryanodine receptors (RyRs) [20][21][22][23], that release Ca 2+ from the endoplasmic reticulum (ER), the most abundant endogenous Ca 2+ reservoir; the acidic Ca 2+ stores of the endolysosomal (EL) system [22]; AA-regulated Ca 2+ (ARC) channels and leukotriene C4 (LTC4)regulated Ca 2+ (LRC) channels, that are contributed from heteromers of the novel Ca 2+ -permeable channels Orai1 and Orai3 and are gated, respectively, by AA itself and its LOX-dependent metabolite LTC4 [24,25]. A recent study showed that Orai3 may mediate AA-and LTC4-dependent Ca 2+ inflow also in human vascular ECs [26], albeit it is not constitutively expressed on the plasma membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Although the mechanism was not thoroughly analyzed, they propose a Ca 2ϩ release-dependent mechanism for activation of this ORAI3 system in which VEGF-mediated Ca 2ϩ release activates cPLA2␣ to catalyze the production of AA, which in turn activates ORAI3 by exposing it to the surface membrane (55). Further studies will be needed to better understand the reciprocal regulation between the "classical" ORAI1-STIM1 SOCE activation and ORAI3 as previously shown for prostate cancer cells (23).…”
Section: Inducing Angiogenesismentioning
confidence: 95%
“…Besides ORAI1-STIM1, a study from the Beech group recently suggested a role for ORAI3 in VEGF-induced EC remodeling with a consequent role for in vitro and in vivo tubulogenesis (55). Although the mechanism was not thoroughly analyzed, they propose a Ca 2ϩ release-dependent mechanism for activation of this ORAI3 system in which VEGF-mediated Ca 2ϩ release activates cPLA2␣ to catalyze the production of AA, which in turn activates ORAI3 by exposing it to the surface membrane (55).…”
Section: Inducing Angiogenesismentioning
confidence: 99%